Prevalence of coronary artery disease before valvular surgery in patients with rheumatic valvular disease - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2012)
Background Although many patients with valvular heart disease have concomitant coronary artery disease (CAD), there are limited data on the association between rheumatic valvular disease (RVD) and CAD. In this study, we aimed to investigate the prevalence of CAD in a group of patients with RVD and undergoing coronary angiography before valvular surgery. Methods In this retrospective analysis, we enrolled a total of 1075 patients (658 women, 61.2%; mean age: 53.2+/-9.9 years) who underwent coronary angiography for the evaluation of CAD before valvular surgery between January 2003 and May 2010. Results The overall prevalence of significant CAD was 11.1%. Patients with significant CAD were older than patients without significant CAD (55.16+/-10.4 vs. 51.45+/-9.1; P<0.001). In addition, hypertension, smoking, diabetes mellitus, and dyslipidemia were more prevalent among patients with significant CAD (P<0.05). After adjustment for several risk factors, only aortic stenosis remained the predictor of significant CAD (odds ratio: 1.66; 95% confidence interval: 1.26-2.19; P<0.001). However, aortic regurgitation was inversely associated with the presence of CAD (odds ratio: 0.56; 95% confidence interval: 0.21-1.01; P<0.001). Conclusion The overall prevalence of CAD in our population with RVD was low. Rheumatic aortic stenosis is associated with an increased prevalence of CAD, whereas the prevalence of CAD is lower in those patients with aortic regurgitation. Coron Artery Dis 23:533-537 (C) 2012 Wolters Kluwer Health vertical bar Lippincott Williams & Wilkins.
Keywords: angiography; coronary artery disease; rheumatic valvular disease; HEART-DISEASE; ALL-CAUSE; ANGINA; MORTALITY